The Influence of Salary, Incentives and Work Discipline on the Performance of Sales Division Employees at PT. Mora Telematika Indonesia - Hendradinata; Pujiati, Herni (Dinasti International Journal of Digital Business Management, 2025)
This study aims to determine the effect of salary, incentives, and work discipline on the performance of sales division employees at PT Mora Telematics Indonesia both partially and simultaneously using SPSS version 24. This research uses quantitative methods by collecting primary data through form to respondents (Sales Division of PT. Mora Telematics Indonesia), then the data is obtained by statistical analysis by conducting instrument tests, namely validity and reliability tests, classical assumption tests, namely multicollinearity test, autocorrelation test, heteroscedasticity test and normality test, multiple linear regression analysis test, hypothesis testing, namely t test and f test and coefficient of determination test. From the results of data analysis shows that 1) Salary has a positive and significant effect on employee performance, it is known that the tcount> ttable value is 2.113> 2.01290 with a significant value of 0.040 <0.05. 2) Incentives have a positive and significant effect on employee performance, it is known that the tcount> ttable value is 2.976> 2.01290 with a significant value of 0.000 <0.05. 3) Work Discipline has a positive and significant effect on employee performance, it is known that the tcount> ttable value is 3.785> 2.01290 with a significance value of 0.005 <0.05. 4) Salary, Incentives, and Work Discipline simultaneously have a positive and significant effect on the performance of sales division employees at PT. Mora Telematics Indonesia with an Fcount> Ftable value of 61,961> 3.20 and a significance value of 0.000 <0.05. And with this, it can also be seen that the results of multiple linear regression tests are Y = 1.531+ 0.243 Incentives, and Work Discipline on the Performance of Employees of the Sales Division of PT Mora Telematics Indonesia with a percentage of 78.4% of the results of the determination coefficient.